2018
DOI: 10.1123/jsep.2017-0244
|View full text |Cite
|
Sign up to set email alerts
|

Within-Person Relationships Between Recreational Running and Psychological Well-Being

Abstract: Participants in the study were recreational runners (N = 244) who maintained online diaries. Once a week for approximately 3 months they indicated how far they had run each day that week, and at the end of the week, they provided measures of their psychological well-being. A series of multilevel modeling analyses (weeks nested within persons) found that well-being, measured in terms of self-esteem, life satisfaction, self-efficacy, meaning in life, and affect, was positively related to how many days people ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Moreover, the satisfaction with one's running progress mediated relationships between well-being and the amount of running. Increase in training led to increase in satisfaction with own progress, which leads to increased personal happiness and well-being [37,38]. This could explain the addiction of ultra-marathoners to running.…”
Section: Ultramarathons-from Extreme To Mainstream: Discussionmentioning
confidence: 99%
“…Moreover, the satisfaction with one's running progress mediated relationships between well-being and the amount of running. Increase in training led to increase in satisfaction with own progress, which leads to increased personal happiness and well-being [37,38]. This could explain the addiction of ultra-marathoners to running.…”
Section: Ultramarathons-from Extreme To Mainstream: Discussionmentioning
confidence: 99%
“…Three 12-week interventions found significantly reduced stress and improvements in mood in college students compared to controls, with more mood improvement in males and in females with higher masculinity [126,130,143]. One 12-week intervention of self-directed running in recreational runners found that well-being was significantly higher during weeks when individuals ran further and ran more often while self-efficacy was related to distance ran but not to frequency of running [143]. Running interventions of 14-20 weeks improved mood and self-esteem and lowered emotional stress reactivity in college/university students compared with controls [116,131,140].…”
Section: Category 3: Longer-term Interventionsmentioning
confidence: 97%
“…A further 10-week running intervention found that, although the exercise group was more likely to use exercise to cope with stress, there were no significant differences in stress or coping measurements between the running and comparison group [123]. Three 12-week interventions found significantly reduced stress and improvements in mood in college students compared to controls, with more mood improvement in males and in females with higher masculinity [126,130,143]. One 12-week intervention of self-directed running in recreational runners found that well-being was significantly higher during weeks when individuals ran further and ran more often while self-efficacy was related to distance ran but not to frequency of running [143].…”
Section: Category 3: Longer-term Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is notably reflected in the increased popularity of unorganized recreational sports such as running [ 4 , 5 ]. Running is known for its low threshold to start: it is relatively inexpensive and easy to practice [ 6 ] and is associated with many health benefits (i.e., musculoskeletal and cardiovascular health, body composition, and psychological state) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and is therefore a popular recreational sport. This popularity is especially apparent in the increasing number of commercial running events, and their growing number of participants.…”
Section: Introductionmentioning
confidence: 99%